Family Support Patterns as Perceived by Shildren with Type 1 diabetes (A study on a Sample of the Age Group 7-11 Years) - Dr .Nagia Hassan Alghriyani (Journal of Scientific and Human Dimensions, 2026)
The study aimed to identify the prevailing patterns of family support as perceived by children with Type 1 diabetes and to uncover the levels of strength and deficiency in these patterns. The study relied on the descriptive-analytical approach, where a questionnaire was applied to a sample of (97) boys and girls with diabetes in the age group (7-11 years) in cooperation with parents. The results showed that the emotional and material aspects are the most prominent in family support, as containment, listening, and the provision of medical and nutritional supplies represent the basic pillar of perceived support. The results also indicated a gap in families’ understanding of the psychological emotions associated with blood sugar fluctuations, which weakens emotional containment in moments of anger and weakness. The informational aspect recorded a tangible deficiency, as the level of empowering the child with self-management skills—such as reading devices and understanding symbols—decreases compared to the strength of verbal and encouraging support. The study concluded that family support is based on parental care and protection and lacks the empowerment and independence strategies that must be granted to the child; the study recommends the necessity of designing training programs to develop the child’s practical skills.".